Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
Zad 6.
(aₙ) = (√2)ⁿ
aₙ₊₁ - aₙ = (√2)ⁿ⁺¹ - (√2)ⁿ = (√2)ⁿ(√2 - 1) > 0 dla każdego n ∈ N
Ciąg ten jest rosnący.
Zad 7.
a₂ = 2, a₄ = 6
a₄ - a₂ = 2r
4 = 2r
r = 2
a₁ = a₂ - r = 2 - 2
a₁ = 0
S₁₀ = (a₁ + a₁₀)/2 * 10
a₁₀ = a₁ + 9r = 0 + 18 = 18
S₁₀ = (0 + 18) * 5
S₁₀ = 90
Odp: a₁ = 0, r = 2, S₁₀ = 90.
Zad 8.
x² = 4y, |q| < 1, q = x/4
2(x+1) = y + 5
y = 2x -3
x² = 8x - 12
x² - 8x + 12 = 0
Δ = 64 - 48 = 16 ⇒ √Δ = 4
x₁ = (8-4)/2 = 2 spełnia założenie
x₂ = (8+4)/2 = 6 nie spełnia założenia
x = 2, y = 2*2 - 3 = 1
Odp: x = 2, y = 1.
Zad 9.
7 + 9 + 11 + ... + x = 432
a₁ = 7, r = 2, aₙ = 7 + 2(n-1), n ∈ N
x = 7 + 2(n-1) = 2n + 5
(7 + 2n + 5) / 2 * n = 432 //*2
n(2n+12) = 864
2n² + 12n - 864 = 0
n² + 6n - 432 = 0
Δ = 1764 ⇒ √Δ = 42
n₁ = (-6-42)/2 < 0 nie spełnia założenia
n₂ = (-6+42) / 2 = 18 spełnia założenie
x = 2*18 + 5 = 41
Odp: x = 41.
Zad 10.
sinα = 28 / 100 = 7/25
cosα = 96 / 100 = 24/25
tgα = 28/96 = 7/24
ctgα = 24/7
sinβ = 24/25
cosβ = 7/25
tgβ = 24/7
ctgβ = 7/24